Applications of low-temperature crystallography - Billing, David Gordon (My University, 1991)
Two cryostats, a liquid nitrogen gas flow cryostat and a Be walled flow cryostat, suitable for use on Enraf Nonlus CAD4 four circle diffractometers have been commissioned and tested. The necessary techniques relating to crystal mounting and centring tor low-temperature data collection were also developed, The complete experimental procedure was tested by determining the crystal structures of the following three compounds at low-temperatures:N-arylpyrrolidin-2-one,4-p-hydroxyphenyl- 9,10,11-trihydroxy-8-ethyl-1,7-dioxaspiro[4,4]-nona-2,6-dione and 5,6-trans-Bromo- 5-hydroxy-3-nitrobicyclo[2,2.2]oct-2-ene.ln performing these structure determinations, some of the applications of low-temperature crystallography were considered.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg for the Degree of Master of Science January, 1991.
Keywords: Crystallography